Pengaruh Harga, Kualitas Pelayanan Dan Store Atmosphere Terhadap Kepuasan Pelanggan - Dwi Wanda Apriliana Putri; Adcharina Pratiwi Pratiwi (JURNAL MANAJEMEN DAN BISNIS, 2024)
The advent of contemporary lifestyles has precipitated a surge in the number of coffee shops, which have become pivotal sites for social interaction and work. In light of the pivotal role coffee shops play in contemporary society, it is crucial to gain insight into the factors that shape consumer satisfaction. The degree of consumer loyalty to a product, in this case coffee, is significantly influenced by the level of satisfaction experienced by the customer. The objective of this study is to gain insight into the influence of price, service quality and shop atmosphere on customer satisfaction at Sarang Kopi Susu Café in Karanggede, Boyolali. This research employs a mixed-methods approach, integrating both qualitative and quantitative techniques. The research population comprised all customers of the Sarang Kopi Susu Café. A sample of 100 respondents was selected using purposive sampling. The data were analysed using multiple linear regression analysis, a t-test, an F-test and a coefficient of determination (R²). The results of this study indicate that variable X1, namely price, has a positive but insignificant effect on customer satisfaction. Conversely, the variables of service quality and store atmosphere have a significant effect on customer satisfaction at Cafe Sarang Kopi Susu Karanggede, Boyolali.